2015
DOI: 10.7863/ultra.15.14.09063
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial of Virtual Reality Simulation Training for Transvaginal Gynecologic Ultrasound Skills

Abstract: The quality of virtual vaginal images produced by inexperienced trainees was greater immediately after a single virtual reality simulation training session than after a single theoretical teaching session.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 8 publications
0
42
0
Order By: Relevance
“…49,50 A similar theme is also visible in the FAST examination performed by emergency medicine residents. 51 …”
Section: Diagnostic Utilitymentioning
confidence: 70%
“…49,50 A similar theme is also visible in the FAST examination performed by emergency medicine residents. 51 …”
Section: Diagnostic Utilitymentioning
confidence: 70%
“…Achieving competencies within medical training is challenging for trainees and their tutors . Chao et al have investigated whether VR simulation can overcome this challenge.…”
Section: Resultsmentioning
confidence: 99%
“…Achieving competencies within medical training is challenging for trainees and their tutors . Chao et al have investigated whether VR simulation can overcome this challenge. This study investigated the impact of VR simulation training compared with theoretical learning on producing transvaginal ultrasound images .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 14 studies in the review, only 5 included a control group, and only 2 of those were randomized. Since this publication, multiple controlled randomized trials have reported the potential benefits of ultrasound simulators . In addition, ultrasound simulators allow trainees to practice multiple times the same ultrasound modality without the need of supervisors or models.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence regarding the use of ultrasound simulators to teach trainees is encouraging. In many studies, students who trained with simulators perform as well or better than their colleagues who trained with instructors …”
mentioning
confidence: 99%